Combining immunotherapy with transarterial radioembolization - BALABAN GENÇ, ZEYNEP CEREN; SOYDEMİR, EFE; ÖNEŞ, TUNÇ (My University, 2023)
Abstract Hepatocellular carcinoma (HCC) has a high mortality rate due to the diagnosis of patients at advanced stages and ineffective systemic therapies. Immunotherapy is considered a new treatment option for unresectable HCC alternatives to the limitations of conventional cytotoxic chemotherapy. In this case report, we reported that transarterial radioembolization and immunotherapy such as atezolizumab and bevacizumab can be used together in a manner effectively in the management of HCC treatment. Keywords: Atezolizumab, fluorodeoxyglucose positron emission tomography‑computed tomography, hepatocellular carcinoma, transarterial radioembolization
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji ve Ultrason Teknolojisi; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Radyoloji, Nükleer Tıp ve Görüntüleme; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Radiological and Ultrasound Technology; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Radiology, Nuclear Medicine and Imaging; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine